Evaluating the Effect of Pulse Width Modulation-Controlled Spray Duty Cycles on Cotton Fiber Quality Using Principal Component Analysis - Joe Mari Maja; Jyoti Neupane; Van Patiluna; Gilbert Miller; Aashish Karki; Michael W. Marshall; Matthew Cutulle; Jun Luo; Edward Barnes (AgriEngineering)
The optimization of cotton defoliant application is critical for enhancing fiber quality and yield. This study aims to assess the impact of different defoliant duty cycles on cotton fiber quality by applying Principal Component Analysis (PCA) to High-Volume Instrument (HVI) data from two fields. Three duty cycles—20%, 40%, and 60%—along with a control treatment were evaluated. PCA was used to identify the key factors influencing cotton quality, with a focus on parameters such as fiber length, strength, and uniformity. The results revealed that the 40% duty cycle consistently produced the most stable and uniform cotton fiber quality across both fields, minimizing variability in critical parameters. In contrast, the 20% and 60% duty cycles, as well as the control, introduced greater variability, with the control treatment showing the most significant outliers. These findings suggest that a 40% duty cycle is optimal for balancing effective defoliation with high-quality cotton production. Future research should explore the robustness of the 40% duty cycle across different environmental conditions and investigate the integration of advanced technologies to further optimize defoliant applications. This study provides valuable insights for improving cotton production practices and ensuring consistent fiber quality.